Factors influencing the desire for orthodontic treatment among patients and parents – A cross-sectional study - Munnal Gulzar; Laiba Amin; Asma Muhammad Yousuf; Afeefa Abul Barakaat; Mubassar Fida; Rashna Hoshang Sukhia (Journal of the Pakistan Medical Association, 2026)
Objective: To assess treatment preferences and perceived barriers related to orthodontic care among children, adolescents, adults and parents. Method: The cross-sectional study was conducted at the Aga Khan University Hospital, Karachi, from April to September 2024, and comprised participants who were allocated to children, adolescents, adults and parents groups. A validated questionnaire was used to survey the motivation for and barriers to initiating orthodontic treatment. The participants rated their pre-treatment pictures and severity of perceived need on a visual analogue scale. Index of orthodontic treatment need comprising dental health and aesthetic components, was used to clinically assess the patient’s orthodontic treatment need. The association of different factors with the severity of treatment need was assessed. Data was analysed using SPSS 23. Results: Of the 136 subjects, 83(61%) were females and 53(39%) were males. There were 34(25%) subjects in each of the four groups with varying age groups. Aesthetic appearance emerged as the primary motivation for initiating orthodontic treatment among 26(76.5%) children, 20(58.8%) adolescents, 27(79.4%) adults and 22(64.7%) parents. The most cited expectation from treatment was improvement of overall facial aesthetics, reported by 20(58.8%) children, 19(55.9%) adolescents, 25(73.5%) adults and 19(55.9%) parents. The most reported barrier to initiating treatment was the anticipated duration of treatment, cited by 14(41.2%) adults and 9(26.5%) adolescents, while fear of anticipated pain was reported by 12 (35.3%) children. All the groups rated the pre-treatment appearance at a median score of 50, and the treatment needed as severe (80-85%). Binomial logistic regression analysis revealed no significant association. However, the odds of having severe treatment need were 1.5 times higher in adults compared to children, 4.9 times higher for functional needs than aesthetic, and 8.3 times higher for forwardpositioned teeth than to enhance facial appearance. Conclusions: The aesthetic component was found to be the primary motivation for seeking orthodontic treatment across all the study groups, reflecting a strong treatment desire, while key barriers included treatment duration, fear of anticipated pain. Key Words: Treatment need, Orthodontics, Malocclusion, Treatment expectations.